Reversal of Diabetes and Metabolic Disorders After Bariatric Surgery - Manco, Melania; Leccesi, Laura; Mingrone, Geltrude (Current Nutrition & Food Science, 2007)
Prevalence of morbid obesity is dramatically increasing over the world. The failure of medical and behavioural treatments has lead to the widespread development of surgical techniques for the resolution of morbid obesity and its comorbidities. The present review highlights the effect of two of these techniques, the Roux-en-Y gastric bypass (RYGB) and the Biliopancreatic Diversion (BPD), on metabolic co-morbidities, which mainly include diabetes mellitus, non alcoholic fatty liver disease and polycystic ovary syndrome. Among the other bariatric techniques currently used, these above mentioned procedures result to be the most effective in obtaining a stable weight loss and the fully resolution of comorbidities. They act by different mechanisms, which are largely still unidentified. The former is a restrictive technique, which causes a reduction in the alimentary flow. The latter induces a prevalent lipid malabsorption. Most Authors agree that surgery modifies the hormonal milieu, acting at several sites, which include the entero-insular axis, the muscle and the adipose tissues. Thereby, we examine the most significant studies performed in animals and humans aiming to compare changes in beta cell function and whole body glucose uptake following restrictive or malabsorptive surgery. Weighting the beneficial effects of bariatric surgery against short- and long-term complications, bariatric surgery seems to be the most effective therapy for severe obesity and type 2 diabetes mellitus.
Keywords: PolyCystic Ovary Syndrome (PCOS)